Modelagem computacional de misturas asfálticas com a utilização do método dos elementos finitos, da teoria da viscoelasticidade linear e da mecânica do dano contínuo - Almeida, Francisco José Pereira de (2019)
A formulation was developed for computational modeling of asphalt mixtures using the Finite Element Method, the Linear Viscoelasticity Theory and the Mechanics of Continuous Damage. The formulation admits loss of stiffness in the material during the fatigue phenomenon due to isotropic or orthotropic damage. The aggregates are considered elastic materials and the Fine Aggregates Matrix (FAM) a linear viscoelastic material. In addition, it is considered that the damage occurs only in the FAM. The homogenized stiffness mechanical properties of Hot Mix Asphalt mixtures (HMA) are obtained, in complex module simulation, from the properties of their individual constituents. It is calculated the number of cycles until the occurrence of failure during the simulation of the fatigue test in virtual bodies submited to cyclical forcing. The inputs are the aggregate gradation curve of the HMA and the mechanical properties of its constituents, defined by the modulus of elasticity of the aggregates and its Poisson ratio; the relaxation modulus of the FAM, for a given temperature, and its Poisson ratio. For damage analysis, in addition to the mentioned stiffness properties, it is also necessary to provide the integrity curve (C x S) of the FAM and the curve GR x Nf , related to the FAM fatigue failure criterion. The simulation results demonstrate the consistency of the formulation. Developed tools allow to capture effects of changes in the properties of the constituents on the behavior of the viscoelastic composite.